Pendekatan Sistem Dalam Pengembangan Sekolah di UPT SD Negeri 060806 - Maulidayani M; Zulqaidah Z; Hasriyati Harahap; Nurroyian N; Agung M. Nur; Fachri Habib (Madani: Jurnal Ilmiah Multidisiplin, 2023)
School development is one form of school leadership position that is very important that a school must have. This research aims to understand the systems approach in school development, the role of leadership in school development, the obstacles faced by school principals and teachers in preparing learning programs, communication between teachers and the community and parents of students, the role of facilities and infrastructure services in development. It was found that the approach to developing the school at SDN 060806 had been implemented well with the help of the collaboration of the school principal, teachers and students. The results of this school can develop students' potential, creativity, interests and talents by providing a platform for them with sufficient capacity.